Infant Mortality in the Chechen Republic: Comparative Analysis and Major Trends - Dmitry O. Ivanov; Karina E. Moiseeva; Kazbek S. Mezhidov; Vadim K. Yuriev; Kseniya G. Shevtsova; Anna V. Alekseeva; Vyacheslav M. Bolotskikh ("Paediatrician" Publishers LLC, 2024)
Background. Despite the clear trend towards infant mortality decrease in our country, there are significant differences in values in some federal districts and regions of Russian Federation. Thus, the assessment of infant mortality rates and health indicators is crucial topic of scientific analysis. Objective. The aim of the study is to investigate selected child health indicators and infant mortality rates in the Chechen Republic. Methods. We have conducted the retrospective cross-sectional study of infant mortality rates, prematurity incidence, infant and newborn morbidity, and mortality of children born sick or got sick. The study was based on the data from official statistics and from the extraction of statistical reporting forms No. 12 and No. 32. Results. The Chechen Republic belongs to the regions with high infant mortality rate, however, it has decreased by 11.6% from 6.9 to 6.1‰ in 2018-2022. The major diseases causing lethal outcomes in infants in this region, and in Russia as a whole, were certain conditions that occur in the perinatal period, and congenital disorders. Meanwhile, mortality from respiratory diseases and some infectious and parasitic diseases exceeded the national average. Prematurity incidence in the republic was 1.5 times lower than the national average, newborns morbidity was 1.7 times lower, infants morbidity was 4.0 times lower. Trend analysis has revealed that prematurity incidence and newborns morbidity have slightly changed over 5 years (+2.2% and -1.0%), while infants morbidity had significant trend (-40.2%). All morbidity rates of children who died at the age under 1 year were significantly lower than the national average for all classes of diseases that are the most common for infants mortality. The mortality rates among children born sick or got sick were on average 5.4 times higher than similar indicators in Russia. The highest mortality rate was observed among children who died from perinatal conditions, congenital disorders, external causes, and some infectious and parasitic diseases. The level of the maternal and child health service performance was 0.44 on average over the 5-year interval, that corresponds to the average level of efficacy. Conclusion. This study has allowed to reveal that there is an urge to improve the organization of medical care for infants in the Chechen Republic.